2012
DOI: 10.1021/jf3028396
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactoglobulin as a Molecular Carrier of Linoleate: Characterization and Effects on Intestinal Epithelial Cells in Vitro

Abstract: The dairy protein β-lactoglobulin (βlg) is known to bind hydrophobic ligands such as fatty acids. In the present work, we investigated the biological activity in vitro of linoleate once complexed to bovine βlg. Binding of linoleate (C18:2) to bovine βlg was achieved by heating at 60 °C for 30 min at pH 7.4, resulting in a linoleate/βlg molar binding stoichiometry of 1.1, 2.1, and 3.4. Two types of binding sites were determined by ITC titrations. Binding of linoleate induced the formation of covalent dimers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…However, uptake and bioavailability of FA may be altered depending on the food matrix (Kushibiki et al, 2001, Mu, 2008, Singh et al, 2009. We observed that linoleate, the salt form of LA, bound to βlg was less bioaccessible compared to free linoleate (Le Maux et al, 2012). After uptake in enterocyte cells, FA are bound to proteins for their intracellular trafficking and thioesterification (Niot et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, uptake and bioavailability of FA may be altered depending on the food matrix (Kushibiki et al, 2001, Mu, 2008, Singh et al, 2009. We observed that linoleate, the salt form of LA, bound to βlg was less bioaccessible compared to free linoleate (Le Maux et al, 2012). After uptake in enterocyte cells, FA are bound to proteins for their intracellular trafficking and thioesterification (Niot et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…Linoleate/βlg complexes were prepared by mixing a solution of βlg and sodium linoleate adapted from Lišková et al (2011) and described by Le Maux et al (2012). Under these conditions complexes with 1, 2 and 3 linoleate bound to βlg are formed.…”
Section: Complex Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, human milk is totally free from β-lactoglobulin and it is reported in whey protein of sheep's, goat's and mare's milk [24]. The percentage of beta lactoglobulin is reported in cow (18.4-20.1%), sheep (59.24 -77.7%) and goat (43.54-63.8%).…”
Section: Lactoglobulinmentioning
confidence: 99%
“…Most of the beneficial effect related to peptides formation through the hydrolysis of whey proteins. These whey peptides is one of the major peptides that are responsible for inhibiting angiotensin converting enzyme, which induces bloodpressure regulating effects [24].…”
Section: Lactoglobulinmentioning
confidence: 99%